Distributed generation control using modified PLL based on proportional-resonant controller - Zare, Ahmad (2020)
Due to the increasing necessity for electrical demand, the microgrids (MGs) based on distributed generations (DGs) within power electronic interfaces are being extended to improve the traditional network control. One of the common ways to achieve the power sharing among the resources on an islanding MG is to use droop control approach, performing based on proportional-integrator (PI) controllers. However, due to the effect of feeder impedance, obtaining the reactive power sharing using this method is not accurate and leads to overload in some DGs, results in the output terminal voltage of each DG go out of the allowable range. The second problem arises when the frequency measurement is not performed precisely, leading inaccurate active power sharing, which can be solved by using an improved phase locked loop (PLL). Therefore, the purpose of this paper is to propose an applicable and simple approach based on the use of conventional droop characteristics and a proportional-resonant (PR) controller in a DG control system. Due to the load changes in the microgrid and other contingencies, the proposed PLL-based controller is able to represent supreme performance with low error in several case studies.